2021
DOI: 10.1002/agj2.20709
|View full text |Cite
|
Sign up to set email alerts
|

Grassland productivity estimates informed by soil moisture measurements: Statistical and mechanistic approaches

Abstract: Soil moisture is a fundamental determinant of plant growth, but soil moisture measurements are rarely assimilated into grassland productivity models, in part because methods of incorporating such data into statistical and mechanistic yield models have not been adequately investigated. Therefore, our objectives were to (a) quantify statistical relationships between in situ soil moisture measurements and biomass yield on grasslands in Oklahoma and (b) develop a simple, mechanistic biomass‐yield model for grassla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 101 publications
2
19
0
Order By: Relevance
“…In a different study that used in situ soil moisture data from the entire state of Oklahoma, Krueger et al (2015) www.publish.csiro.au/wf International Journal of Wildland Fire G showed that 90% of large growing season wildfires across all Oklahoma landscapes (forest, shrubland, and grassland) occurred for FAW < 0.40, which matches the threshold for transpiration reduction due to moisture stress in grassland vegetation (Krueger et al 2021). These soil moisture-wildfire relationships were further described using probabilistic models in a subsequent study (Krueger et al 2016).…”
Section: In Situ Soil Moisture Measurementsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a different study that used in situ soil moisture data from the entire state of Oklahoma, Krueger et al (2015) www.publish.csiro.au/wf International Journal of Wildland Fire G showed that 90% of large growing season wildfires across all Oklahoma landscapes (forest, shrubland, and grassland) occurred for FAW < 0.40, which matches the threshold for transpiration reduction due to moisture stress in grassland vegetation (Krueger et al 2021). These soil moisture-wildfire relationships were further described using probabilistic models in a subsequent study (Krueger et al 2016).…”
Section: In Situ Soil Moisture Measurementsmentioning
confidence: 97%
“…Sharma et al (2021), using data from a grassland field study close to the MOISST site, reported that when soil moisture was plentiful (FAW values of at least 0.59), mixed fuel moisture was not related to soil moisture, but it declined as FAW decreased below this threshold. When FAW dropped below 0.40, the transpiration and growth rate of grassland live fuels declined, reflecting the intensification of drought stress (Krueger et al 2021). When FAW declined below 0.36, the greenness of the vegetation, as indicated by the normalised difference vegetation index (NDVI), began to decrease (Sharma et al 2021) (Fig.…”
Section: In Situ Soil Moisture Measurementsmentioning
confidence: 99%
“…We also learned how soil moisture observations can provide an effective indicator of fuel moisture content and curing rate for grassland vegetation (Sharma et al, 2020) and dead fuel moisture content in Sierra Nevada forests (Rakhmatulina et al, 2021). In situ soil moisture measurements have also proven valuable for improving predictions of grassland fuel loads (Krueger et al, 2021), which is significant given the fact that grasslands account for a large portion of the area burned worldwide each year.…”
Section: Looking Deeper At Soil Moisture-wildfire Relationshipsmentioning
confidence: 99%
“…We also learned how soil moisture observations can provide an effective indicator of fuel moisture content and curing rate for grassland vegetation (Sharma et al, 2020) and dead fuel moisture content in Sierra Nevada forests (Rakhmatulina et al, 2021). In situ soil moisture measurements have also proven valuable for improving predictions of grassland fuel loads (Krueger et al, 2021), which is significant given the fact that grasslands account for a large portion of the area burned worldwide each year.…”
Section: Looking Deeper At Soil Moisture-wildfire Relationshipsmentioning
confidence: 99%